Oil-in-Water Emulsion Exhibits Bitterness-Suppressing Effects in a Sensory Threshold Study - Torrico D. (Wiley-Blackwell, 2015)
© 2015 Institute of Food Technologists®. Little is known about how emulsion characteristics affect saltiness/bitterness perception. Sensory detection and recognition thresholds of NaCl, caffeine, and KCl in aqueous solution compared with oil-in-water emulsion systems were evaluated. For emulsions, NaCl, KCl, or caffeine were dissolved in water + emulsifier and mixed with canola oil (20% by weight). Two emulsions were prepared: emulsion 1 (viscosity = 257 cP) and emulsion 2 (viscosity = 59 cP). The forced-choice ascending concentration series method of limits (ASTM E-679-04) was used to determine detection and/or recognition thresholds at 25 °C. Group best estimate threshold (GBET) geometric means were expressed as g/100 mL. Comparing NaCl with KCl, there were no significant differences in detection GBET values for all systems (0.0197 - 0.0354). For saltiness recognition thresholds, KCl GBET values were higher compared with NaCl GBET (0.0822 - 0.1070 compared with 0.0471 - 0.0501). For NaCl and KCl, emulsion 1 and/or emulsion 2 did not significantly affect the saltiness recognition threshold compared with that of the aqueous solution. However, the bitterness recognition thresholds of caffeine and KCl in solution were significantly lower than in the emulsions (0.0242 - 0.0586 compared with 0.0754 - 0.1025). Gender generally had a marginal effect on threshold values. This study showed that, compared with the aqueous solutions, emulsions did not significantly affect the saltiness recognition threshold of NaCl and KCl, but exhibited bitterness-suppressing effects on KCl and/or caffeine. Practical Applications: Understanding the mechanism of human saltiness and bitterness perception becomes important in order to choose an appropriate approach for sodium-reduction problem in foods. We evaluated the sensory detection and recognition thresholds of NaCl, caffeine, and/or KCl in solution and emulsion systems using the forced-choice ascending concentration series method of limits (ASTM E-679-04). Results showed that emulsions did not significantly affect the saltiness recognition threshold of NaCl and/or KCl; however, emulsions had a bitterness-suppressing effect of either caffeine and/or KCl. This finding is useful for understanding the bitterness-suppressing effects of oil-in-water emulsion systems.